1994
DOI: 10.1146/annurev.mi.48.100194.003433
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Rna Control in Bacteria, Phages, and Plasmids

Abstract: Antisense RNA control is now recognized as an efficient and specific means of regulating gene expression at the posttranscriptional level. Almost all naturally occurring cases have been found in prokaryotes, often in their accessory genetic elements. Several antisense RNA systems are now well-understood, and these display a spectrum of mechanisms of action, binding pathways, and kinetics. This review summarizes antisense RNA control in prokaryotes, emphasizing the biology of the systems involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
278
1
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 426 publications
(284 citation statements)
references
References 167 publications
3
278
1
2
Order By: Relevance
“…Mechanisms by which these antisense RNAs affect target RNAs differ. In bacteria, they can block translation by sequestration of ribosome loading sites, promote target RNA decay by creating RNAase substrates, and induce premature termination of transcription (Wagner and Simons, 1994).…”
Section: Are-mediated Stabilization Of Mrnamentioning
confidence: 99%
“…Mechanisms by which these antisense RNAs affect target RNAs differ. In bacteria, they can block translation by sequestration of ribosome loading sites, promote target RNA decay by creating RNAase substrates, and induce premature termination of transcription (Wagner and Simons, 1994).…”
Section: Are-mediated Stabilization Of Mrnamentioning
confidence: 99%
“…Many untranslated RNAs exert regulatory functions in both prokaryotes and eukaryotes+ A subclass of these regulators, called antisense RNAs, affects target RNA function via binding to complementary sequences+ Most antisense RNAs have been identified in prokaryotic cells, mainly in their plasmids, transposons, and bacteriophages (reviewed by Wagner & Simons, 1994;Wagner & Brantl, 1998;Zeiler & Simons, 1998)+ Plasmid R1 belongs to the IncFII group of plasmids whose initiation frequency is controlled by an antisense RNA, CopA+ Synthesis of the replication initiator protein RepA requires translation of a short leader peptide (tap), located upstream of repA. CopA binds to the leader region of the repA mRNA (CopT), located about 80 nt upstream of the repA start codon (Fig+ 1)+ Binding prevents tap translation and thereby repA expression (Blomberg et al+, , 1994Malmgren et al+, 1996)+ The CopA-CopT binding process is viewed as a series of reactions leading to progressively more stable complexes (Persson et al+, 1988(Persson et al+, , 1990a(Persson et al+, , 1990bMalmgren et al+, 1997)+ CopA and CopT are fully complementary and both RNAs contain a major stem-loop structure (II/II9 in Fig+ 1) that is essential for high pairing rates and control (Öhman & Wagner, 1989;Hjalt & Wagner, 1992, 1995+ The initial step involves a transient looploop interaction (kissing complex) between the complementary hairpin loops (Persson et al+, 1990a(Persson et al+, , 1990b)+ Indeed, a truncated CopA (CopI, Fig+ 1), lacking the 59 proximal 30 nt and consisting only of the major stemloop, does not form stable duplexes with CopT, but is capable of competing with CopA for binding (Persson et al+, 1990b)+ It was recently shown that in both CopICopT and CopA-CopT complexes, initial kissing is rapidly followed by more extended intermolecular interactions (Malmgren et al+, 1997)+ Subsequently, the single-stranded region in the 59 tail of CopA pairs with its complement in CopT to yield the stable, inhibitory CopA-CopT complex+ This complex is the dominant product of binding in vitro (Malmgren et al+, 1996(Malmgren et al+, , 1997+ Complete duplex formation is very slow and has been proposed to be irrelevant for control (Malmgren et al+, 1996(Malmgren et al+, , 1997Wagner & Brantl, 1998)+ Different pairing pathways that result in rapid formation of stable antisense-target RNA complexes have been described (Kittle et...…”
Section: Introductionmentioning
confidence: 99%
“…Antisense RNAs are the principal regulators of replication frequency for diverse plasmids of both Gram-positive and Gram-negative origin (Eguchi et al, 1991;Wagner and Simons, 1994). They act by binding to and inhibiting the function of a target RNA.…”
Section: Introductionmentioning
confidence: 99%